Improving the methodology of development of strength qualities of 15-16-year-old judokas - Yuriy Tropin; Natalia Boychenko; Julia Kovalenko (Kharkiv State Academy of Physical Culture, 2021)
Purpose: to improve the methodology of developing strength qualities of 15-16 year-old judoists with the use of dynamic exercises. Material and methods: analysis of scientific and methodological information, Internet sources and generalization of best practices, pedagogical testing; timing; pedagogical experiment, methods of mathematical statistics. 20 judokas, aged 15-16 years, took part in the pedagogical experiment. Athletes were divided into two groups: control and experimental with 10 judokas in each. The pedagogical experiment lasted three months (September - November 2020). Results: it was found that the level of the development of strength qualities largely determines the tactical and technical training of a judoka, the style, and nature of the competitive fight, based on the analysis of scientific and methodological information and generalization of best practices. The control group was engaged in the training program for Children's and Youth Sports School, and the judoists of the experimental group used a set of dynamic exercises in the training process. The exercises were distributed in such a way as to ensure the alternation of the load, mainly for the muscles of the legs, arms, back, abdomen, and general impact. At the beginning of the experiment, the control indicators of strength qualities did not reveal significant differences between the control and experimental groups (p>0,05, the value of t ranges from 0,32 to 1,01). Conclusions: during the experiment it was found that the use of sets of dynamic exercises in the training process has a positive effect on the judokas` strength preparedness. This is evidenced by the results obtained at the end of the experiment, so the judoists of the experimental group have significantly higher indices of strength preparedness in almost all tests (p<0,05, the value of t ranges from 2,10 to 2,34). In the test «Uchi-komi in 30 s» the result is also better in judoists of the experimental group, but it is statistically insignificant (t=1,07; p>0,05), this is since this exercise is specific to judo.